A Bidirectional Nonisolated Multi-Input DC-DC Converter for Hybrid Energy Storage Systems in Electric Vehicles - Akar, Furkan; Tavlasoglu, Yakup; Ugur, Enes; Vural, Bulent; Aksoy, Ismail (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2016)
To process the power in hybrid energy systems using a reduced part count, researchers have proposed several multi-input dc-dc power converter topologies to transfer power from different input voltage sources to the output. This paper proposes a novel bidirectional nonisolatedmulti-input converter (MIC) topology for hybrid systems to be used in electric vehicles composed of energy storage systems (ESSs) with different electrical characteristics. The proposed converter has the ability to control the power of ESSs by allowing active power sharing. The voltage levels of utilized ESSs can be higher or lower than the output voltage. The inductors of the converter are connected to a single switch; therefore, the converter requires only one extra active switch for each input, unlike its counterparts, hence resulting in reduced element count. The proposed MIC topology is compared with its counterparts concerning various parameters. It is analyzed in detail, and then, this analysis is validated by simulation and through a 1-kWprototype based on a battery/ ultracapacitor hybrid ESS.
Keywords: Batteries; bidirectional; hybrid energy storage systems (HESSs); multi-input converter (MIC); ultracapacitors (UCs); AUTOMOTIVE APPLICATIONS; CONTROL STRATEGY; FUEL-CELL; BATTERY; ULTRACAPACITOR; DESIGN; INTEGRATION; PROPULSION; LIFE; Engineering; Telecommunications; Transportation